2014
DOI: 10.1089/cyber.2014.0078
|View full text |Cite
|
Sign up to set email alerts
|

Youth Mental Health Interventions via Mobile Phones: A Scoping Review

Abstract: Mobile phone technologies have been hailed as a promising means for delivering mental health interventions to youth and adolescents, the age group with high cell phone penetration and with the onset of 75% of all lifetime mental disorders. Despite the growing evidence in physical health and adult mental health, however, little information is available about how mobile phones are implemented to deliver mental health services to the younger population. The purpose of this scoping study was to map the current sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 35 publications
2
88
0
1
Order By: Relevance
“…Our results reinforce the importance of developing accessible, developmentally-appropriate mental health preventive interventions for adolescents. (33)…”
Section: Discussionmentioning
confidence: 99%
“…Our results reinforce the importance of developing accessible, developmentally-appropriate mental health preventive interventions for adolescents. (33)…”
Section: Discussionmentioning
confidence: 99%
“…Search terms were informed by previous reviews (Seko et al 2014), and modified following advice from a medical librarian and field experts. The search was conducted by combining five groups of terms (see online Supplementary Table S1) relating to: type of technology (e.g.…”
Section: Information Sources and Search Strategymentioning
confidence: 99%
“…A recent scoping review of youth mental mHealth interventions found that the “flexibility, interactivity, and spontaneous nature” of mHealth interventions encouraged “persistent and continual access to care outside of clinical settings” for transition-aged youth [89]. Emerging evidence suggests that a coach (peer or professional) can improve outcomes using computer-based and mHealth interventions without the need for an intermediary such as parents, a physician, or other service providers [35].…”
Section: Discussionmentioning
confidence: 99%